Marilena Chaui’s Reading of Merleau-Ponty: From the Critique of Humanism to the Praise of Great Rationalism - Santiago, Homero (Sententiae, 2025)
The intellectual trajectory of Marilena Chaui began with a Master’s thesis on the philosophy of Merleau-Ponty. Successfully defended in 1967, it was Brazil’s very first academic study on the French philosopher, and thus vastly influential on the reception of his unique phenomenology in the country. Our aim is to circumscribe the essence of her reflections on Merleau-Ponty, among which one finds a highly original emphasis on the relationship between his thought and so-called Great Rationalism, the latter being cast in an ambivalent role as both a tradition to be overcome and a source of inspiration for a new ontology.